CUTANEOUS SILENT PERIOD IN MYOFASCIAL PAIN SYNDROME - ULUÇ, KAYIHAN; GÜNDÜZ, OSMAN HAKAN; KAHRAMAN KOYTAK, PINAR; ŞENCAN, SAVAŞ; TANRIDAĞ, TÜLİN (WILEY, 2018)
Introduction: An increased response to painful stimuli without spontaneous pain suggests a role of central hyperexcitability of pain pathways in the pathogenesis of myofascial pain syndrome (MPS). In this study we aimed to test the hypothesis that spinal pain pathways are affected in MPS. We used cutaneous silent period (CSP) parameters to demonstrate the hyperexcitability of spinal pain pathways in MPS. Methods: Twenty-nine patients diagnosed with MPS and 30 healthy volunteers were included in the study. The CSP recordings were performed in the right upper and left lower extremities. Results: In both upper and lower extremities, patients had prolonged CSP latencies (P=0.034 and P=0.049 respectively) and shortened CSP durations (P=0.009 and P=0.008, respectively). Discussion: Delayed and shortened CSP in MPS patients implies dysfunction in the inhibitory mechanism of the spinal/supraspinal pain pathways, suggesting central sensitization in the pathogenesis of MPS and supporting our research hypothesis.
Keywords: cutaneous silent period; myofascial pain; nerve conduction; spinal reflex; central sensitization; spinal pain pathways; hyperexcitability; AMYOTROPHIC-LATERAL-SCLEROSIS; QUALITY STANDARDS SUBCOMMITTEE; PRACTICE PARAMETER UPDATE; NATURAL-HISTORY; MULTIDISCIPLINARY CARE; CLINICAL-FEATURES; AMERICAN ACADEMY; RANDOMIZED-TRIAL; ALS; FATIGUE